Legal Accountability for Artificial Intelligence-Based Decisions from a Modern Legal Perspective - Siska Sanjahaya (PT. Anagata Sembagi Education, 2026)
The rapid development of artificial intelligence (AI) technology has penetrated various sectors of human life, from healthcare and finance to law enforcement to government administrative decision-making. The integration of AI into decision-making processes raises a fundamental question in legal science: who is legally responsible when an algorithm-based decision causes harm to a third party. This study examines the construction of legal liability for AI-based decisions from a modern legal perspective, focusing on two main dimensions: the existing normative framework and applicable liability models. The research method used is normative legal research with statutory, conceptual, and comparative approaches. The results show that Indonesia's positive legal framework does not explicitly regulate liability for AI decisions, necessitating comprehensive legislative reform. Furthermore, the product liability and shared liability models are considered the most relevant for application in the AI ​​context to ensure adequate legal protection for the public. This article concludes that a multi-actor approach with a specific regulatory framework for AI is the best solution that aligns with the principles of the rule of law.